2023
DOI: 10.1021/acsami.2c18317
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Functionalization of Graphite for Hydrovoltaic Power Generation

Abstract: The recent discovery of hydrovoltaic devices for power generation has led to a rapid growth into new materials for harvesting energy specifically for this research field. Of the materials investigated, carbon materials have dominated, and graphene oxide (GO) has emerged as the leader. While graphite is conductive, it does not have functional groups to strongly interact with water, and highly functionalized GO forms strong interaction with water to generate necessary surface charges but does not typically have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…9,10 However, macroscopic devices based on nanoma-terials have high cost and are structurally fragile for dynamic fluid flow and volume-changing stresses, which may lead to poor scale-production of carbon nanomaterial-based power generators. 11,12 Low-cost and three-dimensional materials with mechanically robust and self-supporting characteristics have been investigated for water-induced electricity. 13−15 For example, generators based on natural wood blocks 13,14 and biowaste corn stalks 15 can induce open-circuit voltages of several hundred millivolts from water evaporation or ambient humidity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 However, macroscopic devices based on nanoma-terials have high cost and are structurally fragile for dynamic fluid flow and volume-changing stresses, which may lead to poor scale-production of carbon nanomaterial-based power generators. 11,12 Low-cost and three-dimensional materials with mechanically robust and self-supporting characteristics have been investigated for water-induced electricity. 13−15 For example, generators based on natural wood blocks 13,14 and biowaste corn stalks 15 can induce open-circuit voltages of several hundred millivolts from water evaporation or ambient humidity.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon materials show excellent promise in the field of harvesting water energy due to their inherent properties of electrical conductivity and surface tunability. , Among them, low-dimensional carbon materials (e.g., carbon nanoparticles, carbon nanotubes, graphene, etc.) have been widely investigated. , However, macroscopic devices based on nanomaterials have high cost and are structurally fragile for dynamic fluid flow and volume-changing stresses, which may lead to poor scale-production of carbon nanomaterial-based power generators. , Low-cost and three-dimensional materials with mechanically robust and self-supporting characteristics have been investigated for water-induced electricity. For example, generators based on natural wood blocks , and biowaste corn stalks can induce open-circuit voltages of several hundred millivolts from water evaporation or ambient humidity. These self-supporting materials possess the advantages of being renewable, biocompatible, and biodegradable, also providing ideas for the preparation of low-cost and self-supporting water-to-electricity conversion devices.…”
Section: Introductionmentioning
confidence: 99%
“…Georgakilas et al have reviewed covalent addition of organic functionalities to graphene in detail . Oxygen functional groups (carboxyl, hydroxyl, epoxy, and carbonyl) are commonly added to the GNPs by acid treatment or treating with other strong oxidizing agents. , These oxygen groups can serve as sites to facilitate further functionalization . Aoyama et al covalently functionalized reduced graphene oxide (rGO) using trimellitic anhydride (TMA).…”
Section: Introductionmentioning
confidence: 99%
“…Two accepted MEGs models are ion concentration gradient diffusion and flow current models. The ion concentration gradient diffusion model relies on the construction of chemical gradient structures or asymmetric hygroscopicity to drive the directional diffusion of charged ions to generate a potential between both sides of the MEGs architecture. Studies have revealed that the gradient structure can improve the MEGs performance by affecting the ion concentration difference. A highly flexible dual-asymmetric MEGs based on poly­(vinyl alcohol) (PVA) and cotton fabric was developed .…”
Section: Introductionmentioning
confidence: 99%